Cartografía Social: Empoderando Comunidades en Contextos Agropecuarios - Castañeda, Leidy T.; Urbani, Ilaria; Blundo Canto, Genowefa (2024)
This learning note examines the use of social cartography as a participatory research tool in agricultural contexts. Through case studies in Colombia, it highlights how social cartography empowers rural communities by visualizing socio-environmental dynamics and aiding in collective decision-making about land use. The method has been applied in projects involving the dairy, quinoa, and cacao sectors to enhance local capacities, trace supply chains, and foster sustainable practices. Social cartography facilitates local empowerment and contextualized agricultural interventions, supporting innovation and community-driven development.